Iconología de las coyas en la Crónica de Guaman Poma de Ayala, siglo XVII - Palomino Osorio, Patricia Estefany (2020)
Statement of the problem. What is the relationship between the iconological analysis of the coyas through material culture in the Guaman Poma de Ayala chronicle? Objective. Define the relationship between the iconological analysis of the coyas through the material culture of Guaman Poma de Ayala. Background. Alvez (2016); Baulenas (2015); Días (2015); Falconi (2017); Parani (2019); Sanchez (2014); Ulloa (2015). Theoretical framework. Three theories will be used for this investigation; iconological analysis (Panofsky 1957), the coyas (Guaman Poma 1615; Alvez 2016), and material culture (Carreton 2017; Igareda 2011). Methodology. The type of research is applied, of non-experimental design and a quantitative approach. The population was census and includes the 12 plates of the coyas in the work of the chronicler. In which the 36 item checklist was used. Reliability was measured with the KR 20 method through Excel and SPSS software. Results. The coyas wore clothing and a very different lifestyle compared to the rest of the population, having ornamental clothing and even servants, such as the tupu, ystalla, acsu, lliclla, among others. Conclusions. As a general conclusion, it should be mentioned that the relationship between iconological analysis and material culture are related in a way that allows the origin and life of the coyas to be identified. Recommendations. It is suggested to be able to incorporate new topics regarding the thesis elaboration, in order to motivate future researchers.